Rediscovery of Pseudophilautus semiruber, a diminutive shrub frog (Rhacophoridae: Pseudophilautus) from Sri Lanka - Meegaskumbura, Madhava; Manamendra-Arachchi, Kelum; Bowatte, Gayan; Meegaskumbura, Suyama (Zootaxa, 2012)
Ixalus semiruber Annandale, a diminutive (12-mm snout-vent length) frog originally described from the highlands of Sri Lankain 1913, has not been recorded in the succeeding century and is treated as Data Deficient for conservation purposes. Here wereport its rediscovery in Agra-Bopath, a sub-montane forest reserve. Pseudophilautus semiruber is distinguished by a combina-tion of the following characters: size 12.0–13.4 mm SVL; canthal edges rounded; tympanum distinct; vomerine ridge absent;supratympanic fold feebly defined; throat, chest, belly and underside of thigh smooth. It is a high-elevation (1,750 m a.s.l.) diurnal species that inhabits heavily-shaded leaf litter.